Transformation of Advertising Text Writing Lessons through the Project-Based Learning Model: A Constructivist Approach in Vocational Schools - Talitha Sahda Laili; Isah Cahyani; Khaerudin Kurniawan (Journal of Vocational Education Studies, 2026)
Teaching advertising writing in vocational high schools continues to face a gap between students’ linguistic knowledge and the expectations of professional practice. Although students often understand textual structures, they frequently struggle to produce persuasive advertising texts that are contextually appropriate and aligned with creative industry standards. This study aims to develop and examine the effectiveness of a Project-Based Learning (PjBL) model grounded in constructivist principles for advertising writing instruction in vocational education. A Research and Development approach using the ADDIE framework was employed and implemented through limited and extensive trials involving intact vocational classes functioning as experimental and comparison groups. Data were collected through writing performance tests, multimodal product assessment, classroom observations, student questionnaires, and qualitative feedback from industry practitioners acting as guest teachers. Quantitative analysis using paired and independent sample statistical tests indicates a significant improvement in students’ advertising writing performance after the model revision, particularly in message clarity, copywriting effectiveness, and coherence between textual and visual elements. Qualitative findings further reveal increased student learning independence, reflected in greater initiative during planning, revision, and decision-making processes. Industry practitioners’ feedback also contributed to aligning student work with professional communication standards. These findings suggest that the revised PjBL model is effective in supporting advertising writing as a multimodal vocational competence and illustrate how constructivist project-based instruction can bridge classroom learning with professional communication practices.